Natural compounds of Palestine flora. Comparison analysis by static headspace and steam distillation GC-MS of semivolatile secondary metabolites from leaves of cultivated Palestinian Majorana syriaca - Abu-Lafi, Saleh; Odeh, Imad; Dewik, Hasan; Qabajah, Mohammed; Imam, Amin; Dembitsky, Valery M; Hanus, Lumir O (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2007)
BACKGROUND: A comparative analysis by using static headspace (HS) and steam distillation (SD) GC-MS of the volatile and the semi-volatile secondary metabolites from leaves of cultivated Majorana syriaca. METHODS: The essential oils endogenous to cultivated thyme were isolated and identified by HS-GC-MS technology and compared to those from SD-GC-MS. RESULTS: The HS-GC-MS results showed that the Palestinian cultivated thyme is rich in monoterpene hydrocarbons and phenolic monoterpenes such as alpha-phellandrene, alpha-pinene, beta-myrcene, m-cymene, p-cymene, gamma-terpinene, thymol and carvacrol. In all the samples gamma-terpinene, p-cymene, thymol and carvacrol were the most abundant compounds. CONCLUSIONS: HS and SD-GC-MS have proved that most of the cultivated thyme samples examined has thymol isomer as the major phenolic constituent.
Keywords: Thymol; cymeny; Gas Chromatography-Mass Spectrometry; dobromysl (rod); monoterpeny; Thymus Plant; Střední východ; Cymenes; Origanum; thymol; Thymus (rostlina); Monoterpenes; Middle East; Plant Leaves; plynová chromatografie s hmotnostně spektrometrickou detekcí; listy rostlin